Reducing global inequality to secure human wellbeing and climate safety: a modelling study. Issue 2 (February 2023) - Millward-Hopkins, Joel; Oswald, Yannick
Summary: Background: For decades, climate researchers have highlighted the unprecedented emissions reductions necessary if we are to meet global mitigation ambitions. To achieve these reductions, the climate change mitigation scenarios that dominate the literature assume large-scale deployment of negative-emissions technologies, but such technologies are unproven and present considerable trade-offs for biodiversity and food systems. In response, energy researchers have postulated low energy demand scenarios as alternatives and others have developed models for estimating the minimum energy requirements for the provision of decent material living standards considered essential for human wellbeing. However, a key question that our study aims to explore is how a climate-safe, low energy demand future, and universal decent living could be achieved simultaneously, given the magnitude of current global inequalities in energy consumption and technological access. Methods: In this modelling study, we combined data that described current global and regional inequalities in energy consumption with scenarios for low energy demand in 2050, and compared the resulting distributions with estimates of decent living energy, drawing all of this data from published academic literature. Using a threshold analysis, we estimated how much of the 2050 global population would fall below the minimum energy required to support human wellbeing if a low energy demand pathway was followed but inequalities in energy consumption remained as wide as they currently are. We then estimated the reductions in energy inequality and increases in technological equity that were required to ensure that no one falls below decent living energy in a climate-safe future. Finally, we speculated about the implications for global income inequalities. Findings: We found that unprecedented reductions in income and energy inequalities are likely to be necessary to simultaneously secure a climate-safe future and decent living standards for all. If global energy use is reduced enough to ensure climate safety, but the extent of energy inequality remains as it is today, more than 4 billion people will not have access to decent living energy. To avoid this occurrence, after remaining essentially flat for 150 years, the Gini coefficient for income inequality globally might have to fall by a factor of two (ie, to a lower extent than for some of the most egalitarian European countries) and at a rate of reduction more than double that observed in the so-called golden age of capitalism. In the Global South (South America, Central America, south Asia, southeast Asia, east Asia, the Middle East, and Africa) even greater reductions in inequality would be required, unless the average living standards in the Global North (North America, Europe, Australasia, central Asia, and Japan) and in the Global South fully converged, which would require even more substantial reductions in consumption in the Global North than low energy demand scenarios assume. Interpretation: Resolving the contradiction between the current global economic system (with its inherent inequalities) and the need for planetary and human health necessitates transformational change. Reflecting on the limitations of our analysis, we discuss four ways that these global challenges could be met without the need for such drastic reductions in inequality. Funding: The Centre for Research into Energy Demand Solutions and the Leverhulme Trust.